Public-Private Partnerships Contracts - Alsedrah, Maha Nasser; Aldawsari, Norah Nasser (Journal of Economic, Administrative and Legal Sciences, 2019)
The public private partnership (PPP) in the Kingdom of Saudi Arabia has been subject to many challenges, including that the system of competition and government procurement issued in 2007 is an old and traditional system that did not provide for contracting methods that include negotiation between the administrative authority and the contractor. The Kingdom is undergoing a major change that may extend to a regulatory framework that enhances the chances of successful PPPs projects away from the conventional procurement model. PPPs are one of the main components of the National Transition Program Which aims to increase the participation of the private sector in GDP by 2030. The current interest in these contracts is mainly driven by the decline in government revenues due to the decline in oil prices. The main advantages of the PPPs agreements are that they ensure the maintenance of high levels of service without The government carries huge expenses as the Kingdom is the most active MENA country in the area of ​​PPPs. The study concluded that there is a need for the Saudi regulatory framework to be developed in order to achieve greater growth in PPPs, as well as the need to overcome administrative, regulatory and operational obstacles in order to create a more successful real PPPs. The study aimed at finding out the importance of partnership contracts and how to formulate them, to know the experience and benefit of Saudi Arabia in these contracts, and to know the advantages and benefits resulting from the partnerships and the obstacles facing them.